2019
DOI: 10.2147/jmdh.s182356
|View full text |Cite
|
Sign up to set email alerts
|

<p>Perception of palliative medicine by health care professionals at a teaching community hospital: what is the key to a “palliative attitude”?</p>

Abstract: Background: With growing expense in chronic illness and end-of-life (EOL) care, population-based interventions are needed to reduce the health care cost and improve patients’ quality of life. The authors believe that promotion of palliative medicine is one such intervention and this promotion depends on the acceptance of palliative medicine concepts by health care professionals. Aims of the studies: Perception of palliative medicine in chronic illness and in EOL care by healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The reasons for this are undoubtedly multifactorial, but it is possible that this reflects a shift of attitude toward palliative care within the healthcare community. While some research suggests that providers still hold perceptions that palliative care is only appropriate at the end of life, there is a growing body of evidence which demonstrates that physicians have a greater understanding of the role of palliative care and are more confident in referring patients to palliative care services [ 12 , 27 , 28 ]. A recent study analyzing the perceptions of palliative care among healthcare providers before and after implementation of a palliative medicine division found increased attendance in educational activities and increased confidence in palliative care [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this are undoubtedly multifactorial, but it is possible that this reflects a shift of attitude toward palliative care within the healthcare community. While some research suggests that providers still hold perceptions that palliative care is only appropriate at the end of life, there is a growing body of evidence which demonstrates that physicians have a greater understanding of the role of palliative care and are more confident in referring patients to palliative care services [ 12 , 27 , 28 ]. A recent study analyzing the perceptions of palliative care among healthcare providers before and after implementation of a palliative medicine division found increased attendance in educational activities and increased confidence in palliative care [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, Islamic guidance in the form of Fatwa has accorded medical professionals with the ability to undertake DNR decisions in hopeless medical cases irrespective of family and patient preferences [ 24 ]. This could account for studies reporting that Muslim religiosity does not affect views of the religious feasibility of DNR decisions [ 25 ] and palliative medicine among physicians [ 26 ], which highlights the need to account for the capacity of other factors, such as country of origin and country of practice, to overshadow religious beliefs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study analyzing the perceptions of palliative care among healthcare providers before and after implementation of a palliative medicine division found increased attendance in educational activities and increased con dence in palliative care. 25 Within the same study, providers who favored co-management with palliative care held core values that aligned with current concepts, such as advanced care planning. 25 We expect that as the number of palliative care programs in hospitals across the country increases, understanding and acceptance of palliative care amongst providers will continue to grow and foster a new set of beliefs and norms.…”
Section: Main Findingsmentioning
confidence: 95%
“…25 Within the same study, providers who favored co-management with palliative care held core values that aligned with current concepts, such as advanced care planning. 25 We expect that as the number of palliative care programs in hospitals across the country increases, understanding and acceptance of palliative care amongst providers will continue to grow and foster a new set of beliefs and norms. 26 Our results also demonstrated that family and caregivers did not impede recruitment.…”
Section: Main Findingsmentioning
confidence: 95%
See 1 more Smart Citation